Evaluation of Development Projects: a Process-Centered Approach in the Outskirts of Lima, Peru - Yagüe, José L. (2013)
Development cooperation projects work with people involved in processes of change and social transformation. While the main objective of the intervention is the development process itself, the project’s quality will be determined by the way of implementing it. Its success lies in the sustainability of the generated processes and the connection with them by the involved actors. The evaluation analyses both aspects. This article examines the evaluation, under a process approach, of a project on urban agriculture in Lima (Peru). The results show that the use of this approach, which combines different evaluation tools, allows the identification and analysis of the processes with the involved members, providinga better understanding of the real sustainability of the results.